ANALISIS PENGARUH BUDAYA ORGANISASI DAN KOMITMEN KEORGANISASIAN TERHADAP KINERJA PEGAWAI - Niki Kosasih (Jurnal Dinamika Manajemen, 2019)
The research purpose is; 1) to describe organizational culture, organizational commitment and employee performance, and 2) to analyze the effect of organizational culture and organizational commitment on employee performance, both simultaneously and partially. To conduct it, survey is done with sample as many as 73 units were structured questionnaires are used. The result shows that simultaneously, organizational behaviour and organizational commitment effect positively and significantly to employee performance. In relate with this results it is also found R2 is 0,092 (9,2%). Meanwhile, it is known that: 1) organizational culture effect employee performance positively and 2) commitment organization affects employee performance positively. Â  Key Words. Education and Culture Agency, Batanghari, Average Value